Myocardin Is Involved in Mesothelial–Mesenchymal Transition of Human Pleural Mesothelial Cells - Tucker, Torry; Tsukasaki, Yoshikazu; Sakai, Tsuyoshi; Mitsuhashi, Shinya; Komatsu, Satoshi; Jeffers, Ann; Idell, Steven; Ikebe, Mitsuo (American journal of respiratory cell and molecular biology, 2019)
Pleural fibrosis is characterized by severe inflammation of the pleural space and pleural reorganization. Subsequent thickening of the visceral pleura contributes to lung stiffness and impaired lung function. Pleural mesothelial cells (PMCs) can become myofibroblasts mesothelial-mesenchymal transition (MesoMT) and contribute to pleural organization, fibrosis, and rind formation. However, the mechanisms that underlie MesoMT remain unclear. Here, we investigated the role of myocardin in the induction of MesoMT. Transforming growth factor β (TGF-β) and thrombin induced MesoMT and markedly upregulated the expression of myocardin, but not myocardin-related transcription factor A (MRTF-A) or MRTF-B, in human PMCs (HPMCs). TGF-β stimulation notably induced the nuclear translocation of myocardin in HPMCs, whereas nuclear translocation of MRTF-A and MRTF-B was not observed. Several genes under the control of myocardin were upregulated in cells undergoing MesoMT, an effect that was accompanied by a dramatic cytoskeletal reorganization of HPMCs consistent with a migratory phenotype. Myocardin gene silencing blocked TGF-β- and thrombin-induced MesoMT. Although myocardin upregulation was blocked, MRTF-A and MRTF-B were unchanged. Myocardin, α-SMA, calponin, and smooth muscle myosin were notably upregulated in the thickened pleura of carbon black/bleomycin and empyema mouse models of fibrosing pleural injury. Similar results were observed in human nonspecific pleuritis. In a TGF-β mouse model of pleural fibrosis, PMC-specific knockout of myocardin protected against decrements in lung function. Further, TGF-β-induced pleural thickening was abolished by PMC-specific myocardin knockout, which was accompanied by a marked reduction of myocardin, calponin, and α-SMA expression compared with floxed-myocardin controls. These novel results show that myocardin participates in the development of MesoMT in HPMCs and contributes to the pathogenesis of pleural organization and fibrosis.